Inter-industry Wage Dispersion in Portugal: high but falling - Joop Hartog; Pedro Telhado Pereira; José António Cabral Vieira (Institute for the Study of Labor (IZA), 1999)
This paper examines the size of inter-industry wage dispersion in Portugal and compares with other countries. We find that the country has a high inter-industry wage inequality compared with the European standard. Nevertheless, the dispersion reduced over the 1980s and the early 1990s along a process of centralisation of the wage setting. This finding may add to the emerging notion that centralisation reduces inter-industry wage dispersion.
Keywords: J31; 330; Inter-industry wage dispersion; Portugal; centralisation; Sektorale Lohnstruktur; Schätzung; Tarifpolitik; Portugal